PENDIDIKAN POLITIK PEMILIH PEMULA KEPADA SISWA SEKOLAH MENENGAH ATAS DI KABUPATEN KUBU RAYA MENJELANG PEMILU 2024 - Nugrahaningsih, Nurfitri; Anugrah, Akhmad Rifky Setyan; Suratiningsih, Dewi; Wicaksono, Azzomarayosra (Universitas Mataram, 2024)
The simultaneous election agenda in 2024 is an agenda that will soon be implemented in Indonesia. For this reason, the participation of the younger generation, especially those who have entered the age of novice voters, has a strategic role in ensuring that democracy is not only owned by a certain group of elites. This political education activity is a form of service to the community of Kubu Raya Regency, West Kalimantan as an effort to support and uphold healthy democratic practices. This activity aims to provide insight to novice voters regarding the importance of increasing voter participation as well as to reduce the risk of increasing violations of a number of integrity values in facing the 2024 elections. This activity targets 3rd grade students of SMA Bhayangkari Kubu Raya Regency who have entered voting age and are registered as novice voters. By inviting partners of the Kubu Raya Regency Election Supervisory Agency (Bawaslu) to provide material about the election.